An Overview of the Posttranslational Modifications and Related Molecular Mechanisms in Diabetic Nephropathy - Cao, Yu; Yang, Zhao; Chen, Ying; Jiang, Shuai; Wu, Zhen; Ding, Baoping; Yang, Yang; Jin, Zhenxiao; Tang, Haifeng (Frontiers in Cell and Developmental Biology, 2021)
Diabetic nephropathy (DN), a common diabetic microvascular complication, is characterized by its complexity, high mortality, and the lack of effective diagnosis and treatment methods. Many studies focusing on the diagnosis and treatment of diabetes mellitus (DM) and DN have reported that the pathogenesis and pathophysiology of DN are very complex, involving many molecules and abnormal cellular activities. We first review the effect of posttranscriptional modifications on vital molecules involved in DN including NF-κB, Nrf2 and TGF-β. Then, we describe the relationship between these molecules and related abnormal cellular activities in DN. Finally, we discuss some potential directions for DN treatment and diagnosis. The information reviewed here may be significant in the design of further studies to identify valuable therapeutic targets for DN.